One new species and one new Chinese record of Neoperla (Plecoptera: Perlidae) from Mount Shiwandashan of the Guangxi Zhuang Autonomous Region of southern China - Mo, Raorao; Yao, Gang; Wang, Guoquan; Li, Weihai (Zootaxa, 2019)
Two species of the genus Neoperla Needham, 1905 from the Guangxi Zhuang Autonomous Region of southern China are treated, the description of one new species, N. shiwandashana sp. nov., and the first Chinese record of N. yentu Cao & Bae, 2007. Illustrations and color images are provided for each species and the new species is compared with related congeners.